2017
DOI: 10.3892/ol.2017.6290
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of molecular targeted agents for primary small bowel adenocarcinoma: A multicenter retrospective cohort study by the Osaka Gut Forum

Abstract: Abstract. Primary small bowel adenocarcinoma (SBA) is a rare cancer for which effective treatment strategies have not yet been established. The results of previous retrospective studies suggest that chemotherapy contributes to a longer survival time in patients with SBA. However, there are few case reports about the efficacy of molecular targeted agent-containing chemotherapy for SBA. In the present study, the treatment and follow-up data of patients with SBA who received chemotherapy with or without molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…We recently demonstrated that bevacizumab in combination with platinum-based chemotherapy is effective and well-tolerated for metastatic SBA (mSBA) [11], consistent with other reports [12][13][14][15]. Furthermore, Legue et al [15] reported that bevacizumab is effective for metastatic ileal adenocarcinoma (mIA), but it has remained unclear whether bevacizumab is also effective for metastatic duodenal and jejunal adenocarcinoma (mDJA).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…We recently demonstrated that bevacizumab in combination with platinum-based chemotherapy is effective and well-tolerated for metastatic SBA (mSBA) [11], consistent with other reports [12][13][14][15]. Furthermore, Legue et al [15] reported that bevacizumab is effective for metastatic ileal adenocarcinoma (mIA), but it has remained unclear whether bevacizumab is also effective for metastatic duodenal and jejunal adenocarcinoma (mDJA).…”
Section: Introductionsupporting
confidence: 83%
“…We then investigated the PFS and the OS among mDJA patients with high or low VEGF-A expression. The PFS was signi cantly longer in patients with high VEGF-A expression (median [95% CI] 9 months [4][5][6][7][8][9][10]) than in those with low VEGF-A expression (5 months [1][2][3][4][5][6][7], P = 0.018; Figure 1a) and the OS tended to be longer in those with high VEGF-A expression (20 months [15][16][17][18][19][20][21][22][23][24]) than in those with low VEGF-A expression (7 months [5][6][7][8][9][10][11][12][13][14], P = 0.059; Supplemental Figure 3a). In the Bevacizumab+ Platinum Group, the PFS was signi cantly longer in patients with high VEGF-A expression (26 months [15-]) than in those with low VEGF-A expression (5 months [1][2][3][4][5][6][7][8][9], P = 0.001; Figure 1b) and the OS tended to be longer in patients with high VEGF-A expression than in those with low VEGF-A expression (P =...…”
Section: E Cacy Of Bevacizumab-containing Chemotherapy For Patients With Msbamentioning
confidence: 99%
“…Notably, although median OS, PFS, and ORR have been shown to improve among patients receiving bevacizumab versus those who are not given this antibody, this trend fails to convincingly reach statistical significance. In addition, one of these studies 25 shows in a univariate analysis that treatment with bevacizumab is an important prognostic factor for improved survival time.…”
Section: Discussionmentioning
confidence: 99%
“…On scrutiny, only four articles were relevant studies. 2,5,24,25 All four were cohort studies. No randomized controlled trials were available to date.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation